Enhancing English Technical Report Writing for Engineering Students through a Constructivist-Based Program Using Docear Software - El-Naggar, Zeinab Ali; Yehya, Dalia Ibrahim; Abdel-Aziz, Marwa Mohammad (جامعة عين شمس - كلية التربية - الجمعية التربوية لتدريس اللغات, 2023)
This study examines the impact of a constructivist-based program using Docear Software on developing technical report writing skills of the second-year students of the electrical engineering department at the Faculty of Engineering in Shubra, Benha University (N=45) To evaluate the participants' proficiency, the study used a technical report writing skills checklist and a test as well as a list of electrical engineering terminology. Additionally, the researcher developed the constructivist-based program using Docear Software. The study adopted the quasi-experimental design with the pre-post one group design. The findings of this study show statistically significant difference in the technical report writing skills. The program clearly had a significant impact on students' writing skills, as shown by the considerable effect size (η2 = 98) that verify these findings.
Keywords: المهارات الكتابية -- التقارير الفنية -- الهندسة الكهربائية -- طلبة الجامعات